Techno-economic Assessment of Coal to SNG Power Plant in Kalimantan - Riezqa Andika; Valentina Valentina (Universitas Pendidikan Indonesia, 2016)
As the most abundant and widely distributed fossil fuel, coal has become a key component of energy sources in worldwide. However, air pollutants from coal power plants contribute carbon dioxide emissions. Therefore, understanding how to taking care coal in industrial point of view is important. This paper focused on the feasibility study, including process design and simulation, of a coal to SNG power plant in Kalimantan in order to fulfill its electricity demand. In 2019, it is estimated that Kalimantan will need 2446 MW of electricity and it reaches 2518 MW in 2024. This study allows a thorough evaluation both in technology and commercial point of view. The data for the model is gathered through literature survey from government institution reports and academic papers. Aspen HYSYS is used for modelling the power plant consists of two blocks which are SNG production block and power block. The economic evaluation is vary depends on the pay-back period, capital and operational cost which are coal price, and electricity cost. The results of this study can be used as support tool for energy development plan as well as policy-making in Indonesia.